Polarization origin and iron positions in indium doped barium hexaferrites. Issue 1 (January 2018) - Trukhanov, S.V.; Trukhanov, A.V.; Turchenko, V.A.; Trukhanov, An.V.; Trukhanova, E.L.; Tishkevich, D.I.; Ivanov, V.M.; Zubar, T.I.; Salem, M.; Kostishyn, V.G.; Panina, L.V.; Vinnik, D.A.; et al.
Abstract: M-type hexaferrite BaFe12−x Inx O19 ( x = 0.1, 1.2) samples were investigated by high resolution neutron powder diffraction and vibration sample magnetometry in a wide temperature range of 4–730 K. Structural and magnetic parameters were determined including the unit cell parameters, ionic coordinates, thermal isotropic factors, occupation positions, bond lengths and bond angles, microstrain values and magnetic moments. In 3+ cations may be located only in the Fe1 - 2a and Fe2 - 2b crystallographic positions with equal probability for the x = 0.1 sample. At x = 1.2 about half of In 3+ cations occupy the Fe5 - 12k positions whilst the other half are equiprobably located in the Fe1 – 2a and Fe2 – 2b positions. The spontaneous polarization was observed for these compositions at 300 K. The influence of structural parameters on the temperature behavior of Fe 3+ (i) - O 2- - Fe 3+ (j) (i, j = 1, 2, 3, 4, 5) indirect superexchange interactions was established. With the substitution level increase the superexchange interactions between the magnetic positions inside and outside the sublattices are broken which leads to a decrease in the value of the corresponding magnetic moments.